Approximate Solution of Delay Differential Equations Using the Collocation Method Based on Bernstien Polynomials???? ???????? ????????? ????????? ????????? ???????? ?????????? ???????? ??? ??????? ???? ????????? (Baghdad Science Journal, 2011)
In this paper a modified approach have been used to find the approximate solution of ordinary delay differential equations with constant delay using the collocation method based on Bernstien polynomials.